Chinese Rhetoric and Writing An Introduction for Language Teachers - Kirkpatrick, Andy; Xu, Zhichang (Open textbook library., 2012)
The authors of Chinese Rhetoric and Writing offer a response to the argument that Chinese students' academic writing in English is influenced by "culturally nuanced rhetorical baggage that is uniquely Chinese and hard to eradicate." Noting that this argument draws from "an essentially monolingual and Anglo-centric view of writing," they point out that the rapid growth in the use of English worldwide calls for "a radical reassessment of what English is in today's world." The result is a book that provides teachers of writing, and in particular those involved in the teaching of English academic writing to Chinese students, an introduction to key stages in the development of Chinese rhetoric, a wide-ranging field with a history of several thousand years. Understanding this important rhetorical tradition provides a strong foundation for assessing and responding to the writing of this growing group of students.